2018
DOI: 10.14309/crj.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

Double Trouble: A Rare Case of Concurrent Biliary Adenofibroma and Hepatobiliary Mucinous Cystic Neoplasm

Abstract: Biliary adenofibroma and hepatobiliary mucinous cystic neoplasm are exceedingly rare tumors. To our knowledge, no case of co-existent biliary adenofibroma and mucinous cystic neoplasm has been previously reported. We present a patient who was diagnosed with both tumors concurrently. Both can present with abdominal pain, although some are diagnosed incidentally in asymptomatic patients. Imaging and tumor markers can be suggestive, but histologic examination is needed for definitive diagnosis. Both have a propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Currently, although BFs are classified as benign bile duct tumors and precursors by the 2019 World Health Organization tumor classification system[ 5 ], some cases of BF are characterized by malignant transformation, invasion, and even distant metastasis (Tsui et al [ 1 ] first proposed in 1993, postoperative pathology showed malignant transformation in 3 cases[ 6 - 8 ], 3 cases of biliary adenofibroma with invasive carcinoma[ 9 - 11 ], 3 cases were complicated with liver tissue invasion[ 12 - 14 ], 2 cases were complicated with lymph node metastasis[ 15 ], local recurrence occurred in 2 cases[ 16 ]). The clinical manifestations and imaging characteristics of BF are nonspecific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, although BFs are classified as benign bile duct tumors and precursors by the 2019 World Health Organization tumor classification system[ 5 ], some cases of BF are characterized by malignant transformation, invasion, and even distant metastasis (Tsui et al [ 1 ] first proposed in 1993, postoperative pathology showed malignant transformation in 3 cases[ 6 - 8 ], 3 cases of biliary adenofibroma with invasive carcinoma[ 9 - 11 ], 3 cases were complicated with liver tissue invasion[ 12 - 14 ], 2 cases were complicated with lymph node metastasis[ 15 ], local recurrence occurred in 2 cases[ 16 ]). The clinical manifestations and imaging characteristics of BF are nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…Including the present case, 25 cases of BF have been reported to date (Tsui et al [ 1 ] in 1993, Parada et al [ 17 ] in 1997, Haberal et al [ 12 ] in 2001, Akin et al [ 18 ] and Garduño-López et al [ 19 ] in 2002, Gurrera et al [ 20 ] in 2010, Kai et al [ 6 ] and Nguyen et al [ 7 ] in 2012, Jacobs et al [ 13 ] in 2015, Godambe et al [ 9 ]; Thai et al [ 10 ] and Thompson et al [ 15 ] in 2016, Kaminsky et al [ 8 ] and Arnason et al [ 16 ] in 2017, Esteban et al [ 11 ] in 2018, Sturm et al [ 14 ] in 2019), and no differences in sex or age at onset are evident. The mean age at onset is 57.2 ± 17.79 years.…”
Section: Discussionmentioning
confidence: 99%
“…thus far in the medical literature. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Previously reported cases focused on the clinical and pathological features of biliary adenofibroma, while the imaging findings were recorded only sporadically. Currently, MRI is the imaging modality of choice for evaluating a range of intrahepatic tumors.…”
Section: 이선영 등 담도선섬유종의 자기공명영상 소견mentioning
confidence: 99%